Road(s) To Recovery: Restorative Justice And Discourses of Reconciliation in Domestic Violence Cases - Mastrorillo, Alessia (2017)
Restorative justice is a criminal justice system that emphasizes offender rehabilitation and a repairing of the community as a whole, largely through victim-offender reconciliation. Restorative justice policies claim to both emphasize the victims role in the justice process and to hold offenders accountable for their actions. Despite its supposed benefits, feminist scholars struggle with the role of forgiveness in restorative justice practices and its impacts on the victim and often question the overall effectiveness of restorative justice policies as a whole. In this essay, I offer a critique of the restorative justice practices from a feminist perspective. I intend to examine the guidelines and goals of restorative justice practices, with a specific focus on its application to domestic violence cases. I argue that restorative justice practices fail to emphasize and fully account for the victims safety and interests. Furthermore, I argue that the emphasis on reconciliation and forgiveness that characterizes the restorative justice model exploits women's emotions in the maintenance of their own goal of community reconciliation and risks recidivism by suggesting the violence is somewhat fixable. Through my analysis, I contend that a disconnect exists between restorative justices theoretical guidelines and its practical application in domestic violence cases functions to weaken the practice overall. I do not intend to frame restorative justice as a more suitable alternative to the retributive justice system. Rather, I hope that my critique offers an alternative way of understanding restorative justice and acknowledges the gap that can occur between theory and practice